New Chronology for Neolithic Cultures in the Lake Eyasi Basin, Northern Tanzania - Mwitondi, Musa Said; Bushozi, Pastory Magayane (Zamani: A Journal of African Historical Studies, 2024)
There have been several studies on Neolithic Cultures in the Serengeti National. The recovered archaeological materials include domestic and wild fauna remains, potsherds and lithic artefacts, ochre, and stone enclosures, dating between 7200 and 4900 BP. In the East African Rift System (EARS), conventional ages for Neolithic Cultures are inferred from the most extensively researched Neolithic sites in Kenya, where the oldest Nderit ware, cattle and caprine in the Lake Turkana Basin, northern Kenya, date ca. 5200 BP. Studies on the Neolithic of EARS have been structured to fit into the migration or diffusion models that consider the spread of herders and their domesticates as a practice from Northern to Southern Africa. Subsequently, the succession of Neolithic Cultures in northern Tanzania is linked to the demic migration of the “moving frontiers” from Northern Africa with domesticates and Narosura ware who inhabited the Eyasi Basin and its vicinity after 3000 BP. This article employs a non-probabilistic sampling technique to select the excavation units and datable samples from the Lake Eyasi Basin. It presents new Accelerator Mass Spectrometry (AMS) radiocarbon dates from the Eyasi Basin. The AMS radiocarbon results from this study indicate that Neolithic Cultures have existed in the basin since the late fifth millennium BP, hence pushing back the timing of the introduction of a herding economy in the region to at least a millennium.